O040 A Partner Notification Bureau in action: outcomes for centralised management of positive gonorrhoea and chlamydia results from primary care by a sexual health service. (30th June 2016) - Bell, Gill
Abstract : Background/introduction: Centralised management of positive results by a 'Partner Notification Bureau' has been suggested by the National Chlamydia Screening Programme. From September 2014 positive results for chlamydia and gonorrhoea from primary care were reported directly to the sexual health service in a UK city for management. Aim(s)/objectives: To evaluate the effectiveness of centralised management of treatment and partner notification (PN) by assessing outcomes for the first year and to estimate impact on health adviser workload. Methods: Health adviser records were reviewed retrospectively to assess outcomes in terms of : patients informed of their result, confirmed treated at any service, and offered PN discussion; partners attended. Results: Gonorrhoea: between September 2014 and August 2015 there were 46 positives reported (31 female). Forty five were informed, confirmed treated, and had a PN discussion by phone. The number of partners reported or verified attended per case was 0.8 (37/46). Chlamydia: Between September 2014–August 2015, 457 positives were reported (352 female). Of these, 440 (96%) were informed and had PN discussion, and 448 (98%) were confirmed treated. The number of partners reported or verified attended per case was 0.98 (450/457). Outcomes for both exceeded the national PN standard of 0.6 partners attending per case. Partner notification workload increased by approximately 10%. Conclusion: Centralised management of gonorrhoea and chlamydia positives from primary care resulted in excellent treatment rates and PN outcomes. However, additional health adviser resources are required to manage the extra workload.